A switchable multimode microlaser based on an AIE microsphere. Issue 34 (21st July 2021) - Song, Fengyan; Zhang, Chunhuan; Dong, Haiyun; Fan, Yuqin; Wu, Ming-Yu; Shan, Guogang; Lai, Puxiang; Gao, Hui; Zhao, Yong Sheng; Chen, Sijie
Abstract : A wavelength-switchable microlaser can be easily fabricated using environment-sensitive aggregation-induced emission luminogens (AIEgens) as the optical gain material. Abstract : Switchable multimode microlasers are of great significance to the development of photonic devices with high integration levels. Herein, we demonstrate an acid/alkaline gas-responsive multimode AIEgen@starch microsphere-based microlaser. The aggregation-induced emission (AIE) active fluorescent dye ASCPI was used as the gain medium in this study. ASCPI was weakly emissive in water but became highly emissive when introduced to a starch microsphere as a guest molecule. The resultant ASCPI@starch microsphere worked well as a typical whispering-gallery-mode microlaser. The laser mode wavelengths were size-dependent. Due to the sensitivity of ASCPI to pH, the output of the microlaser could be switched to a shorter wavelength by acetic acid vapor treatment or a longer wavelength by NH3 vapor treatment. This work will provide useful enlightenment for the rational design of effective switchable lasers using AIE materials with simple preparation procedures.